Catalytic Pyrolysis of Waste Biomass - Grigore Pșenovschi; Mihaela Cîlțea-Udrescu; Andreea-Luiza Mîrț; Constantin Neamțu; Gabriel Vasilievici (Proceedings)
The pyrolysis process converts lignocellulose organic materials into gases, liquids (bio-oil), and solids (biochar) [...]